Becoming Nicole : the transformation of an American family - Nutt, Amy Ellis (New York : Random House, 2015)
"The inspiring true story of a transgender girl, her identical twin brother, and an ordinary American family's extraordinary journey to understand, nurture, and celebrate the uniqueness in us all, from the Pulitzer Prize-winning science reporter for The Washington Post. When Wayne and Kelly Maines adopted identical twin boys, they thought their lives were complete. But it wasn't long before they noticed a marked difference between Jonas and his brother, Wyatt. Jonas preferred sports and trucks and many of the things little boys were "supposed" to like; but Wyatt liked princess dolls and dress-up and playing Little Mermaid. By the time the twins were toddlers, confusion over Wyatt's insistence that he was female began to tear the family apart. In the years that followed, the Maineses came to question their long-held views on gender and identity, to accept and embrace Wyatt's transition to Nicole, and to undergo an emotionally wrenching transformation of their own that would change all their lives forever. Becoming Nicole chronicles a journey that could have destroyed a family but instead brought it closer together. It's the story of a mother whose instincts told her that her child needed love and acceptance, not ostracism and disapproval; of a Republican, Air Force veteran father who overcame his deepest fears to become a vocal advocate for trans rights; of a loving brother who bravely stuck up for his twin sister; and of a town forced to confront its prejudices, a school compelled to rewrite its rules, and a courageous community of transgender activists determined to make their voices heard. Ultimately, Becoming Nicole is the story of an extraordinary girl who fought for the right to be herself. Granted wide-ranging access to personal diaries, home videos, clinical journals, legal documents, medical records, and the Maineses themselves, Amy Ellis Nutt spent almost four years reporting this immersive account of an American family confronting an issue that is at the center of today's cultural debate. Becoming Nicole will resonate with anyone who's ever raised a child, felt at odds with society's conventions and norms, or had to embrace life when it plays out unexpectedly. It's a story of standing up for your beliefs and yourself--and it will inspire all of us to do the same. Advance praise for Becoming Nicole: "Becoming Nicole is a miracle. It's the story of a family struggling with--and embracing--a transgender child. But more than that, it's about accepting one another, and ourselves, in all our messy, contradictory glory. The Maines family is as American as they come. In the journey they take toward authenticity and justice, we see a model for the future of our country, a future in which all of us--mothers and fathers, brothers and sisters--somehow find the courage, and the love, to become our best selves."--Jennifer Finney Boylan, co-chair of GLAAD and author of She's Not There: A Life in Two Genders; "Gripping. a timely, signification examination."--Kirkus Reviews"--
"The Maines were a middle-class, hard-working, politically conservative New England couple whose lives felt complete when they adopted identical twin sons. As toddlers, Jonas was the son Kelly and Wayne Maines expected, but Wyatt was only interested in girls' clothes and toys. By age five, this conflict was tearing Wyatt--and the family--apart. Today, Wyatt is Nicole. She and Jonas are now graduating from high school. This is the story of a journey that could have destroyed a family, but instead united them. It's the story of a mother whose instincts told her her child needed love and help. It's the story of a Republican, NRA-member father who overcame confusion and fear to become a vocal advocate of trans rights. It's the story of a brother who always loved and accepted his sister. And, especially, it's the story of a young girl who found the courage to be herself."--
Mirror image -- Beginnings -- Identical twins -- My boys -- Finally ours -- Gender dysphoria -- Down East -- Things to be careful of -- The pink aisle -- A boy-girl -- Wild in the dark -- Girls with magical powers -- A son and a daughter -- Transitions -- Getting the anger out -- The sexual brain -- The Xs and Ys of sex -- Perpetrating gender -- Nature's anomalies -- Being different -- Becoming Nicole -- A new adversary -- Freak -- The Christian Civic League of Maine -- Defending Nicole -- May I have this dance? -- She's all girl -- Eyes on -- Gender matters -- The transgender brain -- Gender of the heart -- Separate and unequal -- Going stealth -- On the outside looking in -- Puberty begins -- Born this way -- A time for change -- We can't lose -- First kiss -- Small victories -- Someone else's brother -- One step back -- Imagine -- Our story -- Breaking barriers -- Commencement -- Transformation -- As long as she's happy.
Includes bibliographical references.
Stonewall Honor Book in Nonfiction, 2016
Keywords: Transgender people -- United States; Transgender youth -- United States; Gender nonconformity -- United States; Families -- United States